1997
DOI: 10.1038/sj.ejcn.1600398
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a single megadose of vitamin A at delivery on breastmilk of mothers and morbidity of their infants

Abstract: Objectives: To evaluate the effect of vitamin A supplementation 24 h after delivery on breastmilk retinol concentration. Methods: Fifty low income women were randomly assigned to a single oral dose of 209 mmol of Vitamin A or none at delivery. Maternal serum and breastmilk retinol levels and infant morbidity and anthropometry were serially assessed. Results: Mean (95% CI) serum retinol levels increased in the supplemented mothers at 2.77 (2.3, 3.2) compared to 1.15 (0.9, 1.4) mmol/l in controls (P`0.05) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 11 publications
(6 reference statements)
4
57
0
7
Order By: Relevance
“…Two studies conducted in Bangladesh (Roy et al, 1997;Rice et al, 1999) also observed a significant increase in serum retinol levels 3 months after delivery in mothers supplemented with 200 000 IU vitamin A compared with the placebo group. In the study by Roy et al (1997) supplementation was administered 24 h after delivery and in the study by Rice et al (1999) supplementation was administered 1-3 weeks after delivery. However, in contrast to the present study in which we observed that vitamin A supplementation prevented a significant fall in breast milk retinol levels at 3 months after delivery, the three cited studies observed an increase in breast milk retinol levels at the same time point.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Two studies conducted in Bangladesh (Roy et al, 1997;Rice et al, 1999) also observed a significant increase in serum retinol levels 3 months after delivery in mothers supplemented with 200 000 IU vitamin A compared with the placebo group. In the study by Roy et al (1997) supplementation was administered 24 h after delivery and in the study by Rice et al (1999) supplementation was administered 1-3 weeks after delivery. However, in contrast to the present study in which we observed that vitamin A supplementation prevented a significant fall in breast milk retinol levels at 3 months after delivery, the three cited studies observed an increase in breast milk retinol levels at the same time point.…”
Section: Discussionmentioning
confidence: 94%
“…In Indonesia, mothers who received 300 000 IU vitamin A within 1-3 weeks after delivery presented significantly higher mean serum retinol levels compared with the placebo group at 3 months after delivery, that is, 1.39±0.49 and 1.24 ± 0.43 mmol/l, in addition to a lower VAD prevalence, 21 and 33%, respectively (Stoltzfus et al, 1993). Two studies conducted in Bangladesh (Roy et al, 1997;Rice et al, 1999) also observed a significant increase in serum retinol levels 3 months after delivery in mothers supplemented with 200 000 IU vitamin A compared with the placebo group. In the study by Roy et al (1997) supplementation was administered 24 h after delivery and in the study by Rice et al (1999) supplementation was administered 1-3 weeks after delivery.…”
Section: Discussionmentioning
confidence: 98%
“…Although the effect of supplementation on breast milk vitamin concentrations has not been ascertained in this population yet, in one previous trial among HIV-infected women daily supplementation with vitamin A during pregnancy was related to increased breast milk retinol Effect of vitamin supplementation to HIV-infected pregnant women A Baylin et al concentrations at 6 weeks postpartum (Semba et al, 2000). Other trials among presumably HIV-uninfected mothers have reported increases of vitamin A in breast milk following supplementation during pregnancy (Muslimatun et al, 2001) or postpartum (Stoltzfus et al, 1993;Roy et al, 1997;Rice et al, 1999;Bahl et al, 2002). In some of these intervention studies, the increase in breast milk retinol concentrations among supplemented mothers coincided with a reduced prevalence of vitamin A deficiency in the infants at 6 months (Stoltzfus et al, 1993;WHO, 1998;Rice et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…Studies among presumably HIV-uninfected women have shown that supplementation with vitamins A and B12 during early lactation increases the concentrations of nutrients in breast milk and results in improved vitamin status of infants during the first 6 months (Thomas et al, 1979;Sneed et al, 1981;Stoltzfus et al, 1993;Roy et al, 1997;Muslimatun et al, 2001;Bahl et al, 2002). Therefore, it has been proposed that vitamin supplementation to lactating mothers may be an efficient way to improve the vitamin status of both mothers and infants (Stoltzfus et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However the impact of vitamin A supplementation on mortality and morbidity of infants younger than 6 months is less conclusive (Humphrey & Rice, 2000; WHO=CHD Immunisation-Linked Vitamin A Supplementation Study Group, 1998;West et al, 1995). Vitamin A supplementation during lactation has been shown to improve vitamin A status and reduce morbidity of infants through its effect on breast milk (Rice et al, 1999;Roy et al, 1997;Stoltzfus et al, 1993).…”
Section: Introductionmentioning
confidence: 99%